Kinetic Characterization of the WalRK(Spn) (VicRK) Two-Component System of Streptococcus pneumoniae: Dependence of WalK(Spn) (VicK) Phosphatase Activity on Its PAS Domain - Gutu, Alina D. (American Society for Microbiology (ASM), 2010)
The WalRK two-component system plays important roles in maintaining cell wall homeostasis and responding to antibiotic stress in low-GC Gram-positive bacteria. In the major human pathogen, Streptococcus pneumoniae, phosphorylated WalR(Spn) (VicR) response regulator positively controls the transcription of genes encoding the essential PcsB division protein and surface virulence factors. WalR(Spn) is phosphorylated by the WalK(Spn) (VicK) histidine kinase. Little is known about the signals sensed by WalK histidine kinases. To gain information about WalK(Spn) signal transduction, we performed a kinetic characterization of the WalRK(Spn) autophosphorylation, phosphoryltransferase, and phosphatase reactions. We were unable to purify soluble full-length WalK(Spn). Consequently, these analyses were performed using two truncated versions of WalK(Spn) lacking its single transmembrane domain. The longer version (Δ35 amino acids) contained most of the HAMP domain and the PAS, DHp, and CA domains, whereas the shorter version (Δ195 amino acids) contained only the DHp and CA domains. The autophosphorylation kinetic parameters of Δ35 and Δ195 WalK(Spn) were similar [K(m)(ATP) ≈ 37 μM; k(cat) ≈ 0.10 min(−1)] and typical of those of other histidine kinases. The catalytic efficiency of the two versions of WalK(Spn)∼P were also similar in the phosphoryltransfer reaction to full-length WalR(Spn). In contrast, absence of the HAMP-PAS domains significantly diminished the phosphatase activity of WalK(Spn) for WalR(Spn)∼P. Deletion and point mutations confirmed that optimal WalK(Spn) phosphatase activity depended on the PAS domain as well as residues in the DHp domain. In addition, these WalK(Spn) DHp domain and ΔPAS mutations led to attenuation of virulence in a murine pneumonia model.